A Professor at the End of Time : The Work and Future of the Professoriate - Best, John B. (Book collections on Project MUSE., 2017)
A Professor at the End of Time tells one professor's story in the context of the rapid reconfiguration of higher education going on now, and analyzes what the job included before the supernova of technological innovation, the general influx of less-well-prepared students, and the diminution of state and federal support wrought wholesale changes on the profession.